Principal Component of Protein-Dense Catfish-Tempeh Nuggets as a Local Stunting Intervention: Komponen Utama Nugget Tempe Lele Padat Protein sebagai Intervensi Stunting Lokal - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Hasanah, Indah Ayu Nur; Fauzi, Andrian Maulana; Ofsah, Olin Najilah; Udin, Baha (Universitas Lancang Kuning, 2025)
Stunting remains a persistent nutritional challenge in Indonesia, requiring evidence-based, locally developed food interventions that are both nutritious and appealing to children. This study aimed to develop and assess “Nulte,” a catfish-tempeh nugget formulation, as a sustainable, protein-dense local food innovation to support stunting prevention. Three formulations with varying catfish-to-tempeh ratios (1:1, 2:1, and 1:2) were prepared using standardized community-based procedures. Each product underwent proximate composition testing following AOAC methods, and sensory evaluation using a 5-point hedonic scale by 30 untrained panelists (local mothers and children). Data were analyzed statistically using ANOVA, MANOVA, and Principal Component Analysis (PCA) to identify the optimal formulation. Formula 2 (2:1) achieved the highest protein content (15.33 g/100 g), the best sensory acceptance (overall 4.2 ± 0.4), and provided up to 76.65 % of daily protein needs for children aged 1–3 years, significantly outperforming other formulas in energy and taste (p < 0.05). PCA results indicated that Formula 2 showed the strongest clustering between nutritional quality and sensory preference dimensions.These findings demonstrate that Nulte nuggets effectively combine animal and plant proteins into a child-friendly, nutrient-dense product. Their simple preparation and use of locally available ingredients make them a promising scalable intervention for community-level stunting prevention in Indonesia.